Identification of CD68(+) neutrophil granulocytes in in vitro model of acute inflammation and inflammatory bowel disease - Amanzada, Ahmad (e-Century Publishing Corporation, 2013)
CD-68 is widely regarded as a selective marker for human monocytes and macrophages and is commonly used in human pathology studies. The purpose of this study was to investigate the expression of CD-68 in human peripheral blood mononuclear cells (PBMCs), neutrophil granulocytes (NGs) and in inflamed intestinal tissue samples for comparison. PBMCs and NGs were isolated from heparinized human blood samples. Intestinal biopsies were obtained during routine endoscopic procedures from patients with inflammatory bowel disease (IBD), e.g. ulcerative colitis and Crohn’s disease. Gene and protein expression was analyzed by real-time RT-PCR, Western blot and immunohistochemistry. Both PBMCs and NGs preparations contained cells that were positive for CD-68 and either neutrophil elastase (NE), or myeloperoxidase (MPO). CD-68(+)/NE(-)/MPO(-) cells were regarded as monocytes. CD-68 mRNA expression was detected in PBMCs and NGs preparations. With Western blot and by performing immunoprecipitation of cell lysate, we could clearly detect CD-68 in NGs, U-937, THP-1, Hep-G2, Jurkat cells and PBMCs. Identification of inflammatory cells in acutely inflamed colonic mucosa obtained from patients with IBD revealed a strong accumulation of CD-68(+)/MPO(+) cells compared to normal colonic mucosa. The uptake of the marker by phagocytosis was excluded by performing a double staining with CD-163/NE and CD-163/MPO in PBMCs, NGs cultures and in inflamed colonic mucosa. These results identify CD-68(+) NGs in peripheral blood and inflamed colonic mucosa. CD-68 is not only a marker for the macrophages-monocytes but also for NGs.